A70 ACCURACY OF IBD PATIENT WAIT TIME ESTIMATES BY GASTROENTEROLOGISTS IN NOVA SCOTIA. (1st March 2018) - Mathias, H; Heisler, C; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic disease with profound health and socioeconomic burden. Approximately 1 in 150 Canadians live with IBD: the highest prevalence rate in the world. Within Canada, Nova Scotia has the highest age-adjusted incidence and prevalence rates of IBD. High levels of need have translated into prolonged wait times: one of the main indicators of healthcare access. Extended wait time can negatively impact physical and mental health outcomes, as well as patient satisfaction of care. The Canadian Association of Gastroenterology has recommended GI wait times between 2 weeks and 2 months. However, the 2015 audit of the Nova Scotia Health Authority (NSHA) Central Zone shows referred patients are waiting over 2 years to see a specialist. Aims: 1) To determine whether physicians can accurately estimate the length of time that patients have waited between the referral and intake specialist appointment; 2) To examine physician-related factors that may influence the accuracy of wait time estimation. Methods: Luminal gastroenterologists and IBD nurse practitioners practicing within the NHSA Central Zone were administered questionnaires designed to measure practice, practitioner, and systems factors which could influence accuracy of physician wait time estimate. Specialists were asked to estimate the wait time for each of their patients seen that day, based on the level of assigned triage urgency. A retrospective chart review was conducted to verify referral date and wait time duration. Results: A total of six specialists were enrolled as of October 2016. Four (67%) participants were male, with a mean age of 51.60 years (SD=11.06 years). All participants reported working in an academic practice with an existing triage process. Five physicians reported using a central triage system for referrals, while one physician completed personal reviews of referrals. When physicians were asked to estimate the wait time for patients between the referral and seeing specialist, they estimated an average of 32 weeks. According to patient health records, patients waited an average of 49 weeks. When comparing physician-estimated wait times to referral dates a moderate positive association was found (rs =0.542, N=6, p <0.001). Conclusions: Initial results demonstrate a disconnect between perceived patient wait times by specialists and true wait times. These findings support previous research which has suggested, despite increased levels of healthcare expenditure, wait times for medically necessary treatment have not improved. Additional recruitment is ongoing and will allow further analysis of practitioner and system-related factors that effect physician estimates of patient wait times. Funding Agencies: None